EXPERT SYSTEM FOR IDENTIFYING STUDENTS’ BEHAVIOR AND PERSONALITY THROUGH CASED-BASED REASONING AT THE STATE JUNIOR HIGH SCHOOL 5 BANDAR LAMPUNG - Elis Malana; Muhammad Said Hasibuan (Proceeding International Conference on Information Technology and Business, 2020)
Expert system was the system designed to emulate the expertise belonging to experts in answering questions and solving problems. This expert system provided solutions to the problems obtained from dialogues among users. This expert system was used because it contained knowledge, facts, and reasoning techniques to solve the problems and to transfer the experts’ ability to the computer. The expert system brought persons who were not an expert to be able to answer questions, solve problems, and make decisions that are usually made by the experts. The State Junior High School 5 Bandar Lampung was one of the institutions engaged in the educational sector. In principle, The State Junior High School 5 Bandar Lampung always attempted to provide the best learning according to the students’ needs (e.g., giving advice to students in controlling themselves to behave and have a good personality in the school environment). The State Junior High School 5 Bandar Lampung carried out the learning and teaching processes for a long period of time. Moreover, the State Junior High School 5 Bandar Lampung also provided a good-learning quality for students through the expert system for identifying the student behavior and personality in State Junior High School 5 Bandar Lampung. It was expected that the students were able to control themselves in behaving and having good personalities so that they were able to develop the students in the learning processes.Keywords: Expert system, Case-Based Reasoning